Revista SATHIRI: Sembrador Vol. 13, N° 1 _Completa - Comisión de Publicaciones (SATHIRI, 2018)
This number covers topics related to Education and Humanities. Social and Economic Sciences. State, Government and Public Administration. Communication, Information and Engineering. Natural Sciences, Ecology, Agriculture and Tourism. Finally, you can find the publication regulations in our Journal.